1992
DOI: 10.1007/bf00040524
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and transcription analysis of mitochondrial plasmids isolated from cytoplasmic male-sterile lines of Vicia faba

Abstract: Three mitochondrial plasmids (1704, 1695 and 1478 bp) were isolated from sterile cytoplasms of Vicia faba L. and cloned into a bacterial plasmid vector. Their nucleotide sequence was found to be 99 to 100% homologous to their counterparts isolated from a fertile cytoplasm (J.A. Wahleithner and D.R. Wolstenholme, Curr Genet 12 (1987) 55-76). Several overlapping transcripts were localized in the region which is unique to each of the three plasmids. S1 nuclease mapping indicated for all of them several 3' termini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The existence of CRISPR repeats in mitochondria was suggested in one of the earliest publications on the subject (the same article described CRISPR in cyanobacteria for the first time) [ 19 ]. The authors used a set of previously published data on the sequencing of mitochondrial plasmids from Vicia faba L. beans [ 20 ], and their conclusions were further cited by Mojica et al [ 21 ], but these observations were not confirmed in later studies [ 8 ].…”
Section: A History Of the Discovery Of The Main Components Of The Cri...mentioning
confidence: 99%
“…The existence of CRISPR repeats in mitochondria was suggested in one of the earliest publications on the subject (the same article described CRISPR in cyanobacteria for the first time) [ 19 ]. The authors used a set of previously published data on the sequencing of mitochondrial plasmids from Vicia faba L. beans [ 20 ], and their conclusions were further cited by Mojica et al [ 21 ], but these observations were not confirmed in later studies [ 8 ].…”
Section: A History Of the Discovery Of The Main Components Of The Cri...mentioning
confidence: 99%
“…Similarly, mitogenomes of Trifolium L. are relatively compact (294.9–348.7 kb) (Choi, Ruhlman, & Jansen, 2020). In addition to the mitogenome, small mt plasmids were discovered in V. faba (Flamand et al., 1992; Flamand et al., 1993; Wahleithner & Wolstenholme, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In broad bean (rViciafaba L.), three supercoiled plasmids, mtpl (1704 bp), mtp2 (1695 bp) and mtp3 (1478 bp), have been described in fertile (5,6) as well as male sterile (7) lines. They all are transcribed (7) and replicative forms have been observed by electron microscopy (8). Plasmids mtpl and mtp2 share more than 80% homology along two-thirds of their sequences but the region transcribed is the non-homologous portion.…”
Section: Introductionmentioning
confidence: 99%